Chronic myeloid leukemia presenting with isolated thrombocytosis in a pediatric patient: A case report of molecular relapse and therapeutic challenge (Indian Journal of Case Reports, 2026)
Chronic myeloid leukemia (CML) in children typically presents with symptomatic splenomegaly or constitutional symptoms; isolated thrombocytosis as an initial presentation is uncommon. We report an 8-year-old male with CML in chronic phase presenting as an incidental finding of marked thrombocytosis during investigation for headaches. The patient harbored a BCR-ABL b3a2 fusion transcript confirmed by reverse transcriptase polymerase chain reaction. Initial management with imatinib achieved excellent molecular and hematological responses with BCR-ABL negativity at 9 months. Subsequent therapeutic non-adherence resulted in molecular relapse with BCR-ABL reactivation. A further complication arose when imatinib dose reduction resulted in severe refractory thrombocytosis, prompting the introduction of hydroxyurea for rapid cytoreduction. This case highlights diagnostic challenges in recognizing CML with isolated thrombocytosis, the critical importance of adherence to tyrosine kinase inhibitor (TKI) therapy in pediatric CML, and the need for multidisciplinary management when single-agent TKI therapy proves inadequate.